틱톡 패션광고의 특성 및 선호도가 패션 상품의 구매 의도에 미치는 영향 - 중국 20~30대 여성 소비자 중심으로 - 김칠순; Chil Soon Kim; 유묘; Miao Yu (The Research Journal of the Costume Culture, 2022)
We conducted this study to determine the TikTok usage status of Chinese consumers, and the effect of fashion advertisement type preference and TikTok characteristics on fashion product purchase intentions. For this study, we conducted a literature review and survey method. The following conclusions were drawn by collecting data online and performing statistical analysis. Firstly, the period of use was 2-4 years, and 95.1% of people used it for 2-3 hours a day, and 95.1% of the people had a purchasing experience on TikTok. Secondly, the most people were interested in self creating and editing videos in TikTok. With regards to TikTok content, groups aged 30 are significantly more interested in fashion coordination suggestions and influencer’ recommendations than groups aged 20. Thirdly, this study found that the characteristics of TikTok fashion advertisements significantly influenced purchase intention. Among the characteristics of fashion advertisements, this study conclude that the “fashion entertainment” characteristic factor that fashion advertisements are fun and entertaining was the most influential variable on purchase intention, followed by useful information, reliability, and interactivity related to fashion. Fourthly, the types of preferred TikTok fashion advertising had a statistically significant effect on product purchase intention. The influential types of preferred advertising are top view, live advertisement, hashtag challenge, in-feed ads, and sticker ads.